Clinical profile, etiology, management and outcome of serum sodium disturbances in children admitted in PICU - Jayakumar, Balaji; Sambasivam, Ekambaranath (International Journal of Research in Medical Sciences, 2017)
Background: Sodium disorders are common in children who need intensive care, they occur in variety of conditions, may remain unrecognized if not suspected and monitored and result in morbidity and mortality irrespective of primary problem. The aim of the study is to know etiology, management and outcome of sodium disturbances in sick children admitted to pediatric intensive care unit to Institute of Social Pediatrics Stanley Medical College. Methods: This is a hospital based cross sectional study. Two hundred and twenty-seven children in the age group of 1month to 12 years admitted in PICU over the period of 8 months were included in the study. Venous blood sampling is obtained from each patient enrolled in the study and is sent for estimation of electrolytes, blood urea, glucose levels. Serum osmolality (calculated), urine osmolality, urine spot sodium were done in selected patients. Results: Among the 227 children studied, 85 children had sodium disturbances that included both hyponatremia (80 children) and hypernatremia (5 children) The most common cause of hyponatremia is CNS disorder 25 patients (31.25%) followed by poisoning 17. Conclusions: Hyponatremia occurs frequently and should be looked for in all sick children. It is of hypotonic- euvolemic type in almost all the acute infections except diarrhea and should be managed accordingly. They contribute significantly to the mortality and morbidity.